2019 International Conference in Engineering Applications (ICEA) 2019
DOI: 10.1109/ceap.2019.8883496
|View full text |Cite
|
Sign up to set email alerts
|

Intelligent Nutrition in Healthcare and Continuous Care

Abstract: In the healthcare industry, the patient's nutrition is a key factor in their treatment process. Every user has their own specific nutritional needs and requirements. An appropriate nutrition policy can therefore help the patient's recovery process and alleviate possible symptoms. Food recommender systems are platforms that offer personalised suggestions of recipes to users. However, there is a lack of usage of recipe recommendation systems in the healthcare sector. Multiple challenges in representing the domai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 17 publications
(20 reference statements)
0
4
0
Order By: Relevance
“…For this purpose, three levels of quality have been defined: High (H) the articles with a score between 8 and 11, Medium (M) between 5.1 and 7.9, and Low (L) less than 5. After the qualification, we can affirm that within the metrics used in this study, the articles [16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31] are of high impact.…”
Section: Resultsmentioning
confidence: 71%
“…For this purpose, three levels of quality have been defined: High (H) the articles with a score between 8 and 11, Medium (M) between 5.1 and 7.9, and Low (L) less than 5. After the qualification, we can affirm that within the metrics used in this study, the articles [16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31] are of high impact.…”
Section: Resultsmentioning
confidence: 71%
“…Its goal is to provide kids from the age of eight to their early teens with a healthier eating lifestyle which varies according to their age, gender, and other related factors. The study of the authors in ( 9 ) suggested a platform that smartly plans the meals of users according to their health conditions. This platform makes use of machine learning algorithms to function.…”
Section: Related Workmentioning
confidence: 99%
“…This is quite different from our own AI model. Meanwhile, the patients' attitude is also important according to [31] but the most important is Transparency and Traceability in food supply chain as to determine which product is suitable for the patient and choice of food to prevent poisoning [32], [33], [35], [35]. Certainly, the resultant effect of busy life styled-patients may assume unhealthy diets.…”
Section: Related Workmentioning
confidence: 99%